EVALUATION OF NEEM LEAF EXTRACT AND ARABIC GUM AS AN EDIBLE COATTING ON THE SHELF-LIFE OF TOMATO FRUITS - OMAR TURKI MAMDOH ERSHIDAT (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Tomato (Solanum lycopersicum L.) is one of the most important crops in the world, covering an area of 5,167,388 hectares and producing 189,133,955.03 tons/year. Tomato postharvest losses can reach 30-40 % globally, but they are significantly greater in developing nations due to the lack of measures to stop decay brought on by fungi. Fruit coatings can reduce postharvest losses and play a critical role in extending fruit's shelf life. Evaluation of neem leaf extract with or without Arabic gum as edible coating on shelf life of tomato fruits was performed. Tomato fruits were randomly distributed among four immersion treatments: 1st in distilled water only, 2nd in neem leaf extract only, 3rd in Arabic gum solution only and 4th in neem leaf extract followed by drying and reimmersion in Arabic gum solution. Arabic gum-coating treatments and those that combined it with neem leaf extract during storage resulted in improved weight loss, total soluble solids, titratable acidity, and colour parameters for tomatoes. The treatments containing neem leaf extract alone reduced the total number of plaques by about half by the end of the storage period. The coating treatment with a mixture of Arabic gum with neem leaf extract was the best treatment as it proved effective in maintaining the quality characteristics and increasing the shelf life of tomatoes.